The Stain of Errors on the Self - Olson, Carl, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2025., 2024)
Using an interdisciplinary approach to the problem of the self, this study focuses on a gap left by previous philosophers. This shortcoming is related to the nature of the self to commit errors that become part of the identity of the self. These